PCR-based Assay for the Specific Detection of Pseudomonas syringae pv. tagetis using an AFLP-derived Marker - Eun-Sung Song (Research in Plant Disease, 2015)
A PCR method has been developed for the pathovar-specific detection of Pseudomonas syringae pv. tagetis, which is the causal agent of bacterial leaf spots and apical chlorosis of several species within the Compositae family. One primer set, PSTF and PSTR, was designed using a genomic locus derived from an amplified fragment length polymorphism (AFLP) fragment produced a 554-bp amplicon from 4 isolates of P. syringae pv. tagetis. In DNA dot-blot analysis with the PCR product as probe, a positive signal was identified in only 4 isolates of P. syringae pv. tagetis. These results suggest that this PCR-based assay will be a useful method for the detection and identification of P. syringae pv. tagetis.